Mesoporous Silica Nanoparticles as Drug Delivery Vehicles in Cancer - Watermann, Anna (Nanomaterials (Basel), 2017)
Even though cancer treatment has improved over the recent decades, still more specific and effective treatment concepts are mandatory. Surgical removal is not always possible, metastases are challenging and chemo- and radiotherapy can not only have severe side-effects but also resistances may occur. To cope with these challenges more efficient therapies with fewer side-effects are required. One promising approach is the use of drug delivery vehicles. Here, mesoporous silica nanoparticles (MSN) are discussed as biodegradable drug carrier to improve efficacy and reduce side-effects. MSN excellently fulfill the criteria for nanoparticulate carriers: their distinct structure allows high loading capacity and a plethora of surface modifications. MSN synthesis permits fine-tuning of particle and pore sizes. Moreover, drug release can be tailored through various gatekeeper systems which are for example pH-sensitive or redox-sensitive. Furthermore, MSN can either enter tumors passively by the enhanced permeability and retention effect or can be actively targeted by various ligands. PEGylation prolongs circulation time and availability. A huge advantage of MSN is their explicitly low toxic profile in vivo. Yet, clinical translation remains challenging. Overall, mesoporous silica nanoparticles are a promising tool for innovative, more efficient and safer cancer therapies.